Biologically-inspired optimal video streaming over wireless LAN - Baguda, Y. S. (Springer, 2011)
There is dramatic need to achieve optimal performance in wireless multimedia network due to its heterogeneous nature, media content and different quality of service (QoS) requirements from different applications. It is very obvious that supporting multimedia applications and services over wireless is very challenging task, and it requires low complexity and highly efficient scheme to cope with the unpredictable channel condition. In this paper, we develop a biologically-inspired strategy for optimal video streaming application. The optimal parameters configuration selected provide the best QoS settings to enhance the video streaming quality over wireless LAN. The scenario has been simulated in NS-2 environment, it clearly shows that the video quality has been improve by selecting minimum configuration to ultimately support video application. The PSO-based approach outperforms other techniques used to compare the performance of the develop scheme in terms of perceived video quality by more than 0.5dB. The experimental simulation has been used to verify the efficiency and potential application of the PSO in wireless multimedia communication.